Imposter Participants? Towards a Reflexive Epistemology of ‘Suspected Participants’ - Jaime Garcia-Iglesias; Brian Heaphy; Neta Yodovich; Sophie Atherton; Azeem Merchant (International Journal of Qualitative Methods)
There is an increased reliance, since COVID-19, on online methods in qualitative research for participant recruitment and data collection. While online methods have some clear advantages, they have also raised ‘new’ concerns about fraudulent participation in qualitative research that can hamper research rigour. Drawing on a case study of two of our own UK-based projects which investigated intersections of health, sexuality, and social connections during and after the COVID-19 pandemic, this paper critically examines the challenges posed by terms like “imposter” and “fraudulent” participants and suggests instead the use of “suspected participants” to acknowledge the researchers’ role in judging if participants are authentic or not. We argue for a reflexive epistemology that questions normative assumptions about authentic participation and advocate an inclusive but separate analysis of suspect data as an interpretive tool that can enhance rigour, rather than rejecting such data as a problem that needs ‘screening out’.